Ransomware : Penetration testing and contingency planning - Das, Ravindra (Boca Raton, FL : CRC Press, 2024)
Ransomware is a threat variant that has existed for a very long time, contrary to popular belief. Today, ransomware attacks have become much more covert and stealthier than when they first came out. In this book, the author provides an overview of ransomware and the timeline of its evolution. The author also discusses famous ransomware attacks that have occurred, with a special focus on SolarWinds and critical infrastructure before taking a deep dive into penetration testing and how it can be used to mitigate the risks of a ransomware attack from happening. The author also covers incident response, disaster recovery, and business continuity planning. We even look at an appropriate data backup plan as well.
1. Introduction 2. A Technical Review of Ransomware Attacks 3. The Importance of Penetration Testing 4. How to Recover from a Ransomware Attack 5. Conclusion
Includes index.
Ravindra Das is a technical writer in the cybersecurity realm. He does cybersecurity consulting on the side through his private practice, RaviDas.Tech, Inc. He also holds the Certified in Cybersecurity certification from the ISC2.
Keywords: Computer security; Malware (Computer software)